Long-term outcomes of salvage high-dose-rate brachytherapy for localized recurrence of prostate cancer following definitive radiation therapy: a retrospective analysis - Watanabe, Kenta; Kamitani, Nobuhiko; Ikeda, Naoki; Kawata, Yujiro; Tokiya, Ryoji; Hayashi, Takafumi; Miyaji, Yoshiyuki; Tamada, Tsutomu; Katsui, Kuniaki (BMC cancer, 2025)
Salvage high-dose-rate brachytherapy (HDR-BT) is a potential treatment for localized recurrence of prostate cancer following definitive radiation therapy. This study aimed to evaluate the long-term safety and efficacy of HDR-BT alone, without androgen deprivation therapy (ADT), in this patient population. We conducted a retrospective analysis of patients with prostate cancer who developed pathologically confirmed local recurrence after definitive radiation therapy and were treated with salvage HDR-BT alone at Kawasaki Medical School Hospital between 2007 and 2021. The prescribed HDR-BT dose was 22 Gy in 2 fractions. Biochemical relapse-free survival (bRFS), cause-specific survival (CSS), and overall survival (OS) were assessed using the Kaplan-Meier method. Adverse events were evaluated based on the Common Terminology Criteria for Adverse Events. Thirty-five patients were included, with a median follow-up of 66.0 months (range, 8.1-169.1). The 5-year bRFS, CSS, and OS rates were 29.7%, 100%, and 89.3%, respectively. Biochemical recurrence occurred in 21 patients (60.0%). Grade 2 adverse events were reported in eight patients (22.9%), while two (5.7%) experienced grade 3 adverse events. All grade 3 adverse events occurred in patients who had HDR-BT as their initial definitive radiation therapy. Salvage HDR-BT without ADT is a safe and effective treatment option for localized prostate cancer recurrence after definitive radiation therapy. It provides excellent CSS rates with acceptable toxicity while potentially reducing the need for ADT. Further prospective studies are warranted to confirm these findings.